Perceptions and Behaviors of BA Sociology Students Related to their Experiences in Doing a Thesis Study - Quintos, Mark Anthony; Iwayama, Minami (Social Sciences and Development Review, 2024)
By virtue of the Philippines’ Commission on Higher Education’s (CHED) Memorandum No. 40, Series of 2017, Directed Research – or more commonly known as the thesis study – has become a requirement for all students of Bachelor of Arts in Sociology programs in the country. This study recognizes that the thesis requirement is often a difficult endeavor for students and sought to look into the thesis-related experiences of students of the discipline now that it has become mandatory. Graduates of a BA Sociology program from a university in Metro Manila during two academic years (A.Y. 2021-2022 and A.Y. 2022-2023) were invited as respondents to a survey that inquired about three aspects of the thesis experience: (1) their perceptions and experiences regarding the importance of their thesis study, its potential for publication, and their readiness in conducting the terminal requirement; (2) their perceptions and experiences with regard to thesis topics, thesis groupmates, and thesis advisers; and (3) the difficulties they experienced during the conduct of the thesis study and their perceptions regarding the thesis as a BA Sociology terminal requirement. The results of the study demonstrate that BA Sociology graduates whose decision-making processes with regard to the different aspects of the thesis-making experience were governed by practical considerations. The results also suggest that the respondents do not possess a strong research culture despite being graduates of a discipline wherewith, by its very nature as a basic science, research should be a vital element. The author suggests that this lack of a research culture is due to (1) socio-economic, (2) curricular, (3) institutional, and (4) societal factors that impede a proper appreciation of the importance of research.
Keywords: BA Sociology; thesis; Directed Research; Philippines; higher education; research